Řešení multietnického soužití na státní a lokální úrovni na příkladu českého a romského obyvatelstva - Kadeřábková, Jaroslava (Lidé města, 2000)
The author analyzes the attention devoted to the role of civil service when settling the problems of multi-ethnic ancl multi-cultural coexistence in the towns, villages and regions of the Czech Republic. She stresses the importance of an expert analysis and cooperation with specialists in charge of questions of multi-cultural and multi-ethnic coexistence. She deals with the professional questions by using the example of the Romany population. Previous experience with the solution to these problems has indicated that specialists from the civil service are interested in cooperation with academic and research institutes. The cooperation will have to be used more intensively in the future.